PEMANFAATAN MEDIA RUANG GURU SEBAGAI SALAH SATU PLATFORM PENDIDIKAN LUAR SEKOLAH - Raudatussaadah Raudatussaadah; Audy Andini Lubis; Asmariah Hasibuan; Muhammad Sibral Malasi (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
Ruang Guru media has recently become increasingly popular so that many have sprung up as platforms or modern online-based education systems. Ruang Guru Media itself uses an E-learning system which is currently widely implemented because existing technology and the internet make the teaching and learning process more flexible and efficient, not limited by space and time. E-learning itself has actually been introduced in Indonesia since 2002, but for now the popular e-learning system or platform for students in Indonesia is the application from Ruang Guru. Ruang Guru itself is one of the paid non-school education platforms for elementary-high school level students, there are actually a lot of e-learning platforms available, they are even popular and can be accessed for free, but students in Indonesia prefer paid applications from Ruang Guru. to access. Therefore, researchers want to examine more deeply about these reasons, what are the causes and how to use the Ruang Guru application for students. This study aims to analyze the utilization of the teacher's room media as a platform for out-of-school education. From these results it can be concluded that the application from Ruang Guru is liked by many students because it is fun and interesting to use as a learning medium or media to fulfill everyday academic information.